BUDAYA ORGANISASI OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN PROVINSI RIAU - Febri Yuliani, Dodi Asmara, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Organizational Culture of the Ombudsman of the Republic of Indonesia Representative of Riau Province. This study aims to analyze the organizational culture of the Riau Ombudsman as well as institutionalizing tips for the Ombudsman organization to realize the cultural equality. Key informants to the head of the Riau ombudsman and ordinary informants were 10 assistants and 3 clients and 1 civil servant as treasurer from the Ombudsman. This type of research is descriptive. The method of analysis is a qualitative approach. Data analysis methods are reduction, clarification and conclusion. The results of the study found that there were several organizational cultures that developed and institutionalized the Riau Ombudsman institution in achieving its success, namely: mutual respect and mutual trust is the key to a tolerant personality between assistants at the Riau Ombudsman. The success of this organizational culture has occurred from the attitude of the leadership who has a personality of mutual respect and mutual respect between the leadership and between assistants and other staff. To develop and maintain the organizational culture of the Riau Ombudsman institution, there are special tips, namely making leaders as role models, making socialization about organizational culture and choosing job applicants with ethics that are in line with organizational culture.